2019
DOI: 10.4028/www.scientific.net/msf.958.105
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of X-Ray Images to Investigate the Viability of Incorporating Poly(Ethylene-co-Vinyl Acetate) (EVA) Waste in Portland Cement

Abstract: EVA (poly (ethylene-co-vinyl acetate)) is a copolymer widely used in the Brazilian footwear industry, where approximately 18% of the EVA remains as waste, principally after the cutting out of insoles. EVA wastes cannot be recycled or reused for the original purpose, but it may be possible to add them to Portland cement to produce concrete for non-structural applications in constructions. This work presents an analytical technique based on the interpretation of X-ray images to assess the spatial distributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Regarding the effect of reducing can be explained by the fact that the density of MEVA is lower than that of the aggregates, which produces a certain lightness to the concrete in its hardened state. Similar studies such as those by Dulsang et al (2016) and Zhang et al (2018), determined that the compressive strength for 3.00 % of MEVA was the only dose that equaled the standard strength; while Machado et al (2019) and Marques et al (2019) found that the MEVA values above to 10.00 % fail to match the initial standard compressive strength, so they recommend using lower doses.…”
Section: Compressive Strengthmentioning
confidence: 70%
See 1 more Smart Citation
“…Regarding the effect of reducing can be explained by the fact that the density of MEVA is lower than that of the aggregates, which produces a certain lightness to the concrete in its hardened state. Similar studies such as those by Dulsang et al (2016) and Zhang et al (2018), determined that the compressive strength for 3.00 % of MEVA was the only dose that equaled the standard strength; while Machado et al (2019) and Marques et al (2019) found that the MEVA values above to 10.00 % fail to match the initial standard compressive strength, so they recommend using lower doses.…”
Section: Compressive Strengthmentioning
confidence: 70%
“…Among the important characteristics of this material, its density stands out, since it is very light and varies from 12.00 to 80.00 kg/m 3 (Machado et al, 2019;Parra et al, 2019). In addition, it is a material that has gained great popularity in the construction industry (Marques et al, 2019), so today its use in this area is gradually increasing, especially for the production of normal and lightweight concrete (Ioana et al, 2023;Ngassam et al, 2018); including partial replacement of aggregates (Selvakumar et al, 2022); also, to establish lightweight and ultralight concrete (Serelis & Vaitkevicius, 2022;Sldozian et al, 2023); similarly, for the production of lightweight concrete blocks (Carneiro et al, 2020) and even to reduce noise, using lightweight concrete for subfloors (Pacheco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%